MIRIKIZUMAB IMPROVES PATIENT ASSESSMENT OF DISEASE SEVERITY AND CHANGE IN DISEASE ACTIVITY IN PATIENTS WITH MODERATELY TO SEVERELY ACTIVE CROHN'S DISEASE. (22nd January 2022) - Rubin, David; Pollack, Paul; Hunter, Theresa; Shan, Mingyang; Chan, Lai-Shan; Deckard, Deanilee
Abstract: BACKGROUND: Mirikizumab (miri), an anti-IL-23p19 inhibitor, has demonstrated efficacy in patients with ulcerative colitis and moderately to severely active Crohn's disease (CD) in a Phase 2, randomised, double-blind, placebo-controlled study (NCT02891226). This analysis evaluated the effect of miri on patient perception of symptom severity as well as disease activity over 12-week (W) induction and 40W maintenance periods. METHODS: During induction, patients were randomised 2:1:1:2 to placebo (PBO), 200mg, 600mg, or 1000mg miri administered intravenously (IV) every four weeks (Q4W). Patients who received miri during induction and achieved ≥1 point improvement in Simple Endoscopic Score for Crohn's Disease (SES-CD) at W12 were randomised 1:1 to continue induction treatment (IV 200mg, 600mg, 1000mg miri Q4W) or receive 300mg miri Q4W administered subcutaneously (SC) for 40W (maintenance). Because of small patient numbers, the randomised maintenance groups results were combined for those who continued IV induction treatment (All IV-C) and those who received SC treatment (All SC). SES-CD non-improvers and patients who received PBO during induction received 1000mg miri IV Q4W during maintenance. The 6-point Patient's Global Rating of Severity (PGRS) scale (1=none to 6=very severe) was recorded daily on an electronic diary, and the 7-point Patient's Global Rating of Change (PGRC) scale (1=very much better to 7=very much worse) was recorded at W4, 12 and 52. Weekly average score for PGRS was calculated and the change from baseline in miri compared to PBO using a mixed model for repeated measures (MMRM) for induction period. Observed PGRC values at W4, 12 and 52 are presented. RESULTS: Significant reduction in PGRS compared to PBO was observed as early as W4 in patients treated with 600mg miri (least square mean (LSM) difference ± standard error [95% confidence internal]: -0.44 ± 0.2 [-0.84, -0.04], p =0.031), and in all miri treated patients by W12: 200mg (-0.58 ± 0.2 [-1.05, -0.12], p =0.014), 600mg (-0.86 ± 0.2 [-1.31, -0.40], p <0.001) and 1000mg (-0.52 ± 0.2 [-0.89, -0.15], p =0.007) (Table 1). Patients treated with 600mg miri and 1000mg reported greatest numerical improvement in PGRC at W12 (2.6 ± 1.0 and2.5 ± 0.9, respectively) (Table 1). Continued numeric reductions in PGRS and PGRC were observed at W52 in all miri dosing groups (Table 1). Patients treated with PBO/1000mg IV reported similar reductions in PGRS and PGRC at W52 to patients treated with miri from W0–52 (Table 1). CONCLUSION: Mirikizumab treatment improved both patients' self-assessment of disease severity and disease activity as early as week 4 and these improvements were sustained through 52 weeks in patients with moderately to severely active Crohn's disease.